2018
DOI: 10.1021/acsomega.8b00440
|View full text |Cite
|
Sign up to set email alerts
|

Time Trends of Polybrominated Diphenyl Ethers (PBDEs) in Antarctic Biota

Abstract: Polybrominated diphenyl ethers (PBDEs) are “emerged” contaminants that were produced and used as flame retardants in numerous consumer and industrial applications for decades until banned. They remain ubiquitously present in the environment today. Here, a unique set of >200 biotic samples from the Antarctic was analyzed for PBDEs, including phytoplankton, krill, fish, and fur seal milk, spanning several sampling seasons over 14 years. PBDE-47 and -99 were the dominant congeners determined in all samples, const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Because of their ubiquitous presence, bioaccumulation, and toxicity, penta-and octa-BDE mixtures have been restricted in some regions of the world, such as the European Union and some States the United States from 2004, with both PBDEs mixtures entering the Stockholm Convention in 2008. (Markham et al 2018), reported PBDEs analyses for a set of > 200 biotic samples from the Antarctic including phytoplankton, krill, fish, and fur seal milk, spanning several sampling seasons over 14 years. Particularly, BDE-47 and BDE-99 were the dominant congeners found in all samples, constituting > 60% of total PBDEs, as was observed in this study for both birds species.…”
Section: Persistent Organic Pollutantsmentioning
confidence: 99%
“…Because of their ubiquitous presence, bioaccumulation, and toxicity, penta-and octa-BDE mixtures have been restricted in some regions of the world, such as the European Union and some States the United States from 2004, with both PBDEs mixtures entering the Stockholm Convention in 2008. (Markham et al 2018), reported PBDEs analyses for a set of > 200 biotic samples from the Antarctic including phytoplankton, krill, fish, and fur seal milk, spanning several sampling seasons over 14 years. Particularly, BDE-47 and BDE-99 were the dominant congeners found in all samples, constituting > 60% of total PBDEs, as was observed in this study for both birds species.…”
Section: Persistent Organic Pollutantsmentioning
confidence: 99%
“…The second explanation may arise from different feeding habits of the two birds species during their stay in South America. Skuas are more likely to forage on landfills and therefore to be exposed to industrial chemicals (such as PBDEs), while kelp gulls prefer to forage in agricultural areas 23,27,60,61 and kelp gulls (orange bars and dots (in cases where only 1 sample was available)).…”
Section: Discussionmentioning
confidence: 99%
“…The benthic ecosystems of Antarctica are extraordinary not only because of their isolation, but also because these Antarctic species often occupy a unique physiological and ecological position, created by the extreme conditions of the continent 57,58 . However, while existing systematic studies on POP levels in benthic ecosystems in the Artic currently report increasing concentrations 59,60 , such trends have not been properly established in the Antartic 9 , as the characterization of POPs in benthic ecosystems in Antarctica has been unsystematic and showing conflicting results 31 .…”
Section: Pops In Benthic Ecosystems Of Antarctica: the Unknownmentioning
confidence: 99%
See 2 more Smart Citations